Volatile Organic Compounds Gas Sensors Based on Molybdenum Oxides: A Mini Review - Wang, Jingxuan; Zhou, Qu; Peng, Shudi; Xu, Lingna; Zeng, Wen (Frontiers in Chemistry, 2020)
As a typical n-type semiconductor, MoO3 has been widely applied in gas-detection field due to the competitive physicochemical properties and ecofriendly characteristics. Volatile organic compounds (VOCs) are harmful to the atmospheric environment and human life, so it is necessary to timely identify the presence of VOCs in the air. This review briefly introduced the application progress of MoO3-based sensor in VOCs detection. We mainly emphasized the optimization strategies of high performance MoO3, which consists of morphology controlled synthesis and electronic properties functional modification. Besides, the general synthesis methods, gas-sensing properties and mechanism were briefly discussed. In final, the application status of MoO3 in gas-sensing and the challenges still to be solved were summarized.